2014
DOI: 10.1097/ncq.0000000000000035
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Views on Bedside Nursing Handover

Abstract: A study was undertaken to explore patients' experiences and perceptions associated with implementation of bedside nursing handover. Interviews were conducted with patients and analyzed using a directed content analysis. Three themes emerged through which patients described their experience with bedside nursing handover as follows: (1) creating a space for personal connection; (2) "bumping up to speed"; and (3) varying preferences. Health care leaders and nurses can use study findings to tailor strategies to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 25 publications
3
69
0
1
Order By: Relevance
“…However, others argue that confidentiality appeared to be of less concern to consumers than nurses believe (Jeffs et al . ; Lupieri et al . ; McMurray et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, others argue that confidentiality appeared to be of less concern to consumers than nurses believe (Jeffs et al . ; Lupieri et al . ; McMurray et al .…”
Section: Discussionmentioning
confidence: 99%
“…() and Jeffs et al . () also state that involving consumers in handover enhances therapeutic relationships and their continuity. In addition, according to Chaboyer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the report method, the literature is consistent regarding the problems associated with change-of-shift report. The problems include a lack of report consistency and structure, potential failures in communication leading to adverse events, and not allowing the patient to be included in their plan of care (Cairns, Dudjak, Hoffmann, & Lorenz, 2013;Friesen et al, 2013;Jeffs et al, 2014). Much of the literature has found that many medical errors involve actual inaccuracies with communication.…”
Section: Traditional Versus Non Traditional Nursing Reportmentioning
confidence: 99%
“…One negative finding was that the researchers noted varying exposure of patients to the bedside report process; meaning some were there for a short period of time and others there for a much longer hospital stay. (Jeffs et al, 2014).…”
Section: Advantages Of Bedside Reportingmentioning
confidence: 99%
See 1 more Smart Citation